Avaliação do bloqueio duplo do sistema renina-angiotensiva e remodelações cardíaca e renal, em ratos espontaneamente hipertensos, obesos e não obesos - Freitas, Olavo de Carvalho (2008)
The renin-angiotensin system activation has been regarded as more and more important, namely interaction with obesity, by accumulation of visceral adipose tissue, a major risk for hypertension development. Obesity is associated with several abnormalities, such as sodium retention, renal hyperfiltration, left ventricular hypertrophy and microalbuminuria. Objective: To evaluate kidney and heart remodeling, following pharmacological double blockade of the renin-angiotensin system, in spontaneously hypertensive rats, and in normotensive and spontaneously hypertensive obese-induced adult rats. Material and Method: Forty spontaneously hypertensive Wistar rats were subdivided into 4 groups of 10, as follows: 10 animals were treated with pharmacological double blockade of the renin-angiotensin system, and received enalapril and losartan for 4 weeks; 10 non-blocked; 10 rats rendered obese in adult life by means of a hypercaloric diet without block, and 10 hypertensive obese-induced, blocked animals. Forty normotensive rats (controls) were subdivided into 4 groups of 10 animals, as follows: 10 normal rats; 10 normal and blocked; 10 obese-induced without block and 10 obese-induced, blocked. Blood pressure, heart and kidney weights (relatively to body weight), heart and kidney collagen levels, and proteinuria, were evaluated in all animals. Results: Increased heart and kidney weight/body weight and tissue collagen and proteinuria levels were found in hypertensive and obese-hypertensive rats. Pharmacological double blockade of the renin-angiotensin system brought significant reduction (CI 95 %) in heart weight/body weight in obese-hypertensive rats, and reduction of renal collagen levels and proteinuria in hypertensive and obese-hypertensive rats. The normotensive obese rats increased renal collagen levels and proteinuria. Such changes were significantly reduced (CI 95 %) by means of renin-angiotensin system blocked. Conclusions: Pharmacological double blockade of the renin-angiotensin system brings benefits, particularly, to kidney remodeling, with reduction of the proteinuria in hypertensive, hypertensive-obese and normotensive-obese rats.